2015
DOI: 10.1021/acs.jafc.5b03113
|View full text |Cite
|
Sign up to set email alerts
|

Pickering Emulsion Gels Prepared by Hydrogen-Bonded Zein/Tannic Acid Complex Colloidal Particles

Abstract: Food-grade colloidal particles and complexes, which are formed via modulation of the noncovalent interactions between macromolecules and natural small molecules, can be developed as novel functional ingredients in a safe and sustainable way. For this study was prepared a novel zein/tannic acid (TA) complex colloidal particle (ZTP) based on the hydrogen-bonding interaction between zein and TA in aqueous ethanol solution by using a simple antisolvent approach. Pickering emulsion gels with high oil volume fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
169
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 354 publications
(177 citation statements)
references
References 38 publications
7
169
0
1
Order By: Relevance
“…This kind of α-helical spectrum was very similar to that published earlier [29]. CD ellipticity at 221 nm was widely used to estimate α-helix content in the protein structure [30]. In the presence of lecithin, the spectra of zein was changed in ellipticity at 221 nm, which indicated that the interaction between lecithin and zein significantly modulated the secondary structure of zein.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This kind of α-helical spectrum was very similar to that published earlier [29]. CD ellipticity at 221 nm was widely used to estimate α-helix content in the protein structure [30]. In the presence of lecithin, the spectra of zein was changed in ellipticity at 221 nm, which indicated that the interaction between lecithin and zein significantly modulated the secondary structure of zein.…”
Section: Resultssupporting
confidence: 82%
“…Food macromolecules and small molecular compounds are usually used to fabricate food-grade colloidal structures such as colloidal nanoparticles, complexes, and microcapsules, which show good potential for applications in food and beverage industries [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a few works has been available on Pickering emulsions stabilized by a wide range of biological micro-and nano-particles, such as modified starch (Yusoff & Murray, 2011), cellulose nanocrystal (Kalashnikova, Bizot, Cathala, & Capron, 2011), chitin nanocrystal (Tzoumaki, Moschakis, Kiosseoglou, & Biliaderis, 2011), chitosan particles (Liu, Wang, Zou, Wei, & Tong, 2012) and flavonoids (Luo et al, 2012). Limited information is available on Pickering emulsions stabilized by protein-based particles, such as hydrophobic zein colloid particles (de Folter, van Ruijvena, & Velikov, 2012;Wang et al, 2015;Zou, Guo, Yin, Wang, & Yang, 2015), kafirin nanoparticles (Xiao, Li, & Huang, 2015), as well as hydrophilic whey protein microgel particles (Destribats et al, 2014), soy protein nanoparticle aggregates (Liu & Tang, 2013). Gliadins, one of the most abundant storage proteins in cereals, are prolamine-type proteins in wheat.…”
Section: Introductionmentioning
confidence: 99%
“…The ZTP‐stabilised emulsions were prepared as described in our previous study (Zou et al ., ). Zein powders (2.5 g) were dispersed in ethanol‐water solution (100 mL, ethanol:water = 7:3, v/v) and stirred overnight to allow complete hydration.…”
Section: Methodsmentioning
confidence: 97%